QUALITY IMPROVEMENT STUDIES ELECTRICITY AND REDUCTION OF LOSSES IN POWER LINES - Ахмедов Алимжон Махмудович (Web of Journals Publishing, 2024)
The article explores the possibility of using an IGCT thyristor (with an integrated gate) in high-current high-power rectifier systems and STATCOM voltage converters together with series-connected control devices for longitudinal compensation-controlled voltage source CVS that regulate power flows.
Keywords: IGCT -Integrated thyristor with a switched gate; power lines; STATCOM- static synchronous compensator; UPC- Longitudinal Compensation Control Devices.